Integrating The Halal Product Assurance System into The Canvas Business Model of Soedirman Halal Canteen - Hety Handayani Hidayat; Nur Wijayanti; Siswantoro (Universitas Djuanda, 2025)
The Halal Product Assurance System (HPAS) covers a business's entire business process, starting from purchasing materials to products being delivered to consumers. The food industry, including catering services such as restaurants, needs to implement this SJPH to ensure product halalness and increase its competitive advantage. The application of SJPH has an impact on the business strategy being implemented. Based on this relationship, we conducted this research to integrate SJPH into a restaurant business model, namely the Soedirman halal canteen. The business model is designed using a business model canvas which comprehensively describes the running business, while SJPH refers to Decree No. 57 in 2021. he business model with SJPH integration is evident in the value proposition, namely guarantees related to the halalness of its products, so that customer segmentation becomes more specific to the Unsoed and Muslim academics around the campus. Changes can also be seen in customer relations, where the canteen provides halal education for its customers, key partnerships select halal material suppliers, and critical activities include business processes and halal training. Evaluation and monitoring. Another aspect that is imposed is the cost structure, where additional costs exist for implementing and submitting halal. Hopefully, this canvas model can make it easier for the Soedirman halal canteen to operate by implementing SJPH and become an example for other restaurants that want to implement it.